Long survival in a pancreatic carcinoma patient with multi-organ toxicities after sintilimab treatment: A case report - Ni, Chen-Xu; Zhao, Yu; Qian, Hong; Fu, Hui; Yan, Yu-Ying; Qiu, Yu-Shuang; Zhou, Can-Can; Huang, Fang; Shen, Fu-Ming; Li, Dong-Jie; Xu, Qing (Frontiers in Pharmacology, 2023)
Pancreatic carcinoma is the leading cause of death among digestive malignancies in China. In particular, there is no breakthrough in prolonging the survival of pancreatic cancer patients with chemical and targeted therapies. Tumor immunotherapy brings opportunities and progress for the treatment of pancreatic cancer. Sintilimab is an innovative PD-1 inhibitor which was reported certain clinical benefits in multi-line treatments of advanced pancreatic cancer with gemcitabine. The combination therapy of PD-1 with gemcitabine plus high-intensity focused ultrasound (HIFU) in pancreatic cancer has not been reported. Here we report a case of a Chinese old patient diagnosed with metastatic pancreatic cancer. Two months after sintilimab treatment, the patient occurred severe immune colitis. The patient was diagnosed with immune ureteritis after eight months of treatment. The immue-related adverse events (irAEs) refined after timely recognition and correct intervention by the clinician and clinical pharmacist. After first-line treatment of sintilimab plus gemcitabine combined with pancreatic HIFU, the patient achieved a remarkable benefit of 11-month progression-free survival (PFS) and 20-month overall survival (OS). The first-line treatment of sintilimab plus gemcitabine combined with HIFU demonstrates a potential therapeutic effect on metastatic pancreatic carcinoma with tolerable adverse reactions.